GS domain mutations that constitutively activate T beta R-I, the downstream signaling component in the TGF-beta receptor complex. - Wieser, R (1995)
The TGF-beta type II receptor (T beta R-II) is a transmembrane serine/threonine kinase that, upon ligand binding, recruits and phosphorylates a second transmembrane kinase, T beta R-I, as a requirement for signal transduction. T beta R-I is phosphorylated by T beta R-II in the GS domain, a 30 amino acid region preceding the kinase domain and conserved in type I receptors for other TGF-beta-related factors. The functional role of seven serines and threonines in the T beta R-I GS domain was investigated by mutational analysis. Five of these residues are clustered (TTSGSGSG) in the middle of the GS domain. Mutation of two or more of these residues impairs phosphorylation and signaling activity. Two additional threonines are located near the canonical start of the kinase domain, and their individual mutation to valine strongly inhibits receptor phosphorylation and signaling activity. Replacement of one of these residues, Thr204, with aspartic acid yields a product that has elevated in vitro kinase activity and signals anti-proliferative and transcriptional responses in the absence of ligand and T beta R-II. The identification of constitutively active T beta R-I forms confirms the hypothesis that this kinase acts as a down-stream signaling component in the TGF-beta receptor complex, and its activation by T beta R-II or by mutation is necessary and sufficient for propagation of anti-proliferative and transcriptional responses.